Evaluation of Novel Bio-friendly Two-step Process in the Removal of Heavy Metals from the Wastewater - Islam, Mir Sujaul; Md Abdus, Sobahan; R. M., Yunus; Md Abdul, Karim (Bangladesh Botanical Society, 2015)
Two-step treatment technique was developed for the treatment of water by Pseudomonas aeroginosa in a bioreactor in a first phase and then the bacterial treated water was treated with the vetiver grass, cattails and water hyacinth in second phase. Two-step process of bioremediation of 13 days was found to be satisfactory for As, Ba, Cd, Co, Cr, Cu, Hg, Ni, Pb and Zn in compared to the direct treatments with vetiver grass, cattails and water hyacinth in 20 days. As the plants cannot work or tolerate the higher concentrations of heavy metals, so with the first step on an average 52.48% reduction of heavy metals were done within 5 days. It was observed that 100% removal of Pb was found by two-step process of Pseudomas aeroginosa with cattails and water hyacinth, respectively in 13 days, while 98.16% removal of Pb was found by direct plant treatment of water hyacinth in 20 days. It was clear that the two-step treatment for vetiver grass, cattails and water hyacinth were found as the most effective treatments.